Designing and performance analysis of efficient and reliable medium access control protocols for vehicular ad hoc networks - Shah, A.F.M.Shahen (My University, 2020)
Vehicular ad hoc networks (VANETs) have recently attracted interest for automation and intelligent transportation system (ITS). VANETs increase transportation efficiency and road safety. VANETs comprise inter-vehicle communication (V2V, vehicle-to-vehicle) as well as communication between vehicle and infrastructure (V2I, vehicle-to-infrastructure). VANETs facilitate numerous applications which can be categorized as safety messages (sm) and non-safety data (nsd). However, to have useful applications the communication between vehicles and with existing networking infrastructures should be efficient. For any ad hoc network, medium access control (MAC) protocol is one of the most significant parts, because efficient and reliable data transmission directly depends on MAC protocol. The IEEE 802.11p standard is outlined by the institute of electrical and electronics engineers (IEEE) to support wireless access in vehicular environments (WAVE) and to provide MAC and Physical (PHY) Layer specifications for VANETs. Later IEEE 802.11 standard incorporated IEEE 802.11p. In IEEE 802.11p and IEEE 802.11, distributed coordination function (DCF) is the fundamental mechanism to access the medium and enhanced distributed channel access function (EDCAF) is sketched to support contention-based prioritized Quality of Service (QoS) at MAC layer. In this thesis, the performance of DCF and EDCAF for both IEEE 802.11p and IEEE 802.11 is modeled and analyzed. An analytical analysis based on Markov chain model is presented. The derived performance model is justified by numerical results. Then we investigated the xix influence of channel fading and capture effect. Nakagami, Rayleigh, and Rician faded channels are considered. However, both IEEE 802.11p and IEEE 802.11 can not fulfill the performance criteria of VANETs. In VANETs, high mobility and relative mobility among vehicles can result in rapid topology changes with frequent link breakage and unstable communications which cause collision and packet loss. Alternatively, clustering VANETs into small groups which limits channel contention and controls the network topology efficiently. In this thesis, a novel cluster-based MAC (CB-MAC) protocol is proposed for VANETs. The cluster formation process is defined. Moreover, cluster head (CH) election and cluster merging processes are described for efficient communication in the cluster as well as out of the cluster. The mechanism defined in IEEE 802.11 is specially designed for only direct communications and is not suitable for cluster-based communications. Therefore, new control packets are introduced and the existing control packet format is modified to support cluster-based communications. For effective MAC protocol design, the request to send (RTS)/ clear to send (CTS) mechanism is not used for sm which are of broadcast nature. On the other hand, the RTS/CTS mechanism is used for nsd delivery to eliminate hidden node problem. Markov chain model based analytical model is presented to explore the performance of proposed CB-MAC protocol. The proposed protocol is validated by numerical studies. The numerical results exhibit that the proposed CB-MAC protocol improves system performance and satisfies the delay constraint of 100 ms for sm. Another way, cooperative transmission can improve the communication reliability and can enhance communication rate with lower delay by alleviating wireless channel impairments caused by the mobility in VANETs. In this thesis, a novel reliable and efficient cooperative MAC protocol for VANETs (RECV-MAC) is also proposed which is designed both for sm and nsd transmission. RECV-MAC ensures reliable and efficient transmission with the help of helpers which have good channel condition to both the sender and the receiver. New control messages are introduced to support cooperative communication. The mechanism is defined to choose the suitable transmission mode as well as to select the optimal helper. To investigate the performance of the proposed RECV-MAC protocol, Markov chain model based analytical analysis is provided. The proposed RECV-MAC protocol is validated by numerical studies. The performance of the RECV-MAC protocol is compared with the traditional MAC model which is based on the IEEE 802.11p and a quantitative comparison with existing cooperative MAC schemes is presented. It is obvious from the comparison that the RECV-MAC performs better than IEEE 802.11p and existing cooperative MAC schemes. The numerical results demonstrate that the RECV-MAC protocol improves the performance with higher throughput, enhances reliability of communication by decreasing PDR, and xx decreases delay, in particular, satisfies the delay constraint of 100 ms for sm. The performance of IEEE 802.11p, IEEE 802.11, and CB-MAC is optimized. Performance optimization mechanism is presented. The comparison between IEEE 802.11p and IEEE 802.11is provided. The microscopic mobility model is generated in SUMO for practical scenario. Monte Carlo simulation results are presented which verify analytical analysis. Complexity analysis is presented. Comparison between complexity analysis is illustrated.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: IEEE 802.11; IEEE 802.11p; MAC; Optimization; VANETs